Estimation of mangrove sediment carbon storage in Purun Kecil Village, West Kalimantan, Indonesia - Helena, Shifa; Minsas, Sukal; Jayanti, Ucy (Journal of Marine Resources and Coastal Management, 2026)
Mangrove ecosystems play a crucial role as coastal blue-carbon reservoirs, yet widespread land-use conversion has led to substantial degradation and carbon loss in many regions. This study estimates sediment carbon storage in mangrove ecosystems in Purun Kecil Village, Mempawah Regency, West Kalimantan, Indonesia, and identifies sediment factors influencing carbon retention. The research was conducted from June to August 2025, with sediment samples collected at a depth of 0–30 cm across natural mangroves, inactive fishponds, and coconut plantations. Organic carbon was analyzed using the Loss on Ignition (LOI) method, accompanied by measurements of bulk density, soil texture, pH, moisture, and salinity. The results show that natural mangroves stored the highest sediment carbon stock (614.7 Mg C/ha), followed by inactive fishponds (472.0 Mg C/ha) and coconut plantations (392.9 Mg C/ha). One-way ANOVA confirmed significant differences in sediment carbon stocks among land-use types (p < 0.001), and Tukey’s HSD post-hoc analysis indicated that all land-use categories differed significantly. Higher carbon storage in natural mangroves was associated with lower bulk density and finer sediment texture, which promote carbon stabilization under anaerobic conditions. These findings demonstrate that land-use conversion from mangroves to aquaculture and agriculture substantially reduces sediment carbon reserves and degrades soil quality. The study highlights the importance of mangrove conservation and restoration as effective nature-based solutions for climate change mitigation and coastal ecosystem management.